Fabrication and Crystallization of ZnO-SLS Glass Derived Willemite Glass-Ceramics as a Potential Material for Optics Applications. (21st January 2016) - Mohd Zaid, Mohd Hafiz; Amin Matori, Khamirul; Abdul Aziz, Sidek Hj.; Kamari, Halimah Mohamed; Mat Yunus, Wan Mahmood; Abdul Wahab, Zaidan; Samsudin, Nur Farhana
Abstract : Willemite glass-ceramics were successfully derived from conventional melt-quench ZnO-SLS precursor glass by an isothermal heat treatment process. The effect of heat treatment temperatures on the physical properties was investigated by Archimedes principle and linear shrinkage. The generation of willemite crystal phase and morphology with increase in heat treatment temperature was examined by X-ray diffraction (XRD), Fourier transform infrared (FTIR), and field emission scanning electron microscopy (FESEM) techniques. X-ray diffraction revealed that the metastableβ -Zn2 SiO4 and thermodynamically stable zinc orthosilicate α -Zn2 SiO4 phases can be observed at temperatures above 700°C. The experimental results indicated that the density and shrinkage of the glass-ceramic vary with increasing the sintering temperature. FTIR studies showed that the structure of glass-ceramic consists of SiO2 and ZnO4 units and exhibits the structural evolution of willemite glass-ceramics. The characteristic of strong vibrational bands can be related to theS i O 4 4 - tetrahedron corresponding to reference spectra of willemite.